Visualization mobile employee attendance system with near field communication (NFC) technology - Goh, Wen Sen (2014)
The manual punch card device makes administrator faces difficulties in generating attendance reports and verify the correct attendance date and time whenever there is a misaligned or loss of timecard. This report will introduce a system that will overcome the mentioned problems. The employee attendance management system will be developed in java for mobile application (android) and PHP plus JavaScript for web management system. This attendance system will use android based smartphone/tablet to track/record the attendance via NEC tag and update instantly to online database server. The attendance summary will be display in graph and chart to display the attendances in visual form for better view. Besides that, object oriented design pattern and normalized database design will be used to improve maintainability, testability and reusability of the system. NEC technology is used as it provides simple, faster, better security features at very low cost. The attendance system combines the mobile application and web system to provide real time solution and assessable in anytime and anywhere as long as internet access is available. An improvised of employee attendance system is definitely the answer to the client's problems.